Prospective 12-month course of bipolar disorder in out-patients with and without comorbid anxiety disorders. - Otto, M; Simon, N; Wisniewski, SR; Miklowitz, D; Kogan, J; Reilly-Harrington, N; Frank, E; Nierenberg, A; Marangell, L; Sagduyu, K; Weiss, R; Miyahara, S; et al. (2006)
BACKGROUND: The impact of anxiety disorders has not been well delineated in prospective studies of bipolar disorder. AIMS: To examine the association between anxiety and course of bipolar disorder, as defined by mood episodes, quality of life and role functioning. METHOD: A thousand thousand out-patients with bipolar disorder were followed prospectively for 1 year. RESULTS: A current comorbid anxiety disorder (present in 31.9% of participants) was associated with fewer days well, a lower likelihood of timely recovery from depression, risk of earlier relapse, lower quality of life and diminished role function over I year of prospective study. The negative impact was greater with multiple anxiety disorders. CONCLUSIONS: Anxiety disorders, including those present during relative euthymia, predicted a poorer bipolar course. The detrimental effects of anxiety were not simply a feature of mood state. Treatment studies targeting anxiety disorders will help to clarify the nature of the impact of anxiety on bipolar course.